2012
DOI: 10.1016/j.csda.2011.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Covariate unit root tests with good size and power

Abstract: Short excerpts of these working papers may be quoted without explicit permission provided that full credit is given to the source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Ng and Perron () showed that traditional model selection criteria such as the Bayesian or Akaike information criterion (AIC) satisfy the upper bound condition in Assumption 5 and, hence, can be used to select k . Whereas Pesavento () recommended using the value of k selected by minimizing a modified AIC of the type suggested in Ng and Perron () from an univariate regression on the GLS detrended y t , Fossati () showed that forcing the lead and lag orders in () to be equal results in a small power reduction in the tests that can be avoided by removing this constraint.…”
Section: The Test and Asymptotic Distributionsmentioning
confidence: 99%
“…Ng and Perron () showed that traditional model selection criteria such as the Bayesian or Akaike information criterion (AIC) satisfy the upper bound condition in Assumption 5 and, hence, can be used to select k . Whereas Pesavento () recommended using the value of k selected by minimizing a modified AIC of the type suggested in Ng and Perron () from an univariate regression on the GLS detrended y t , Fossati () showed that forcing the lead and lag orders in () to be equal results in a small power reduction in the tests that can be avoided by removing this constraint.…”
Section: The Test and Asymptotic Distributionsmentioning
confidence: 99%
“…A rich literature has discussed the limitations of the testing approach, see among others (DeJong et al, 1992;Schwert, 1989;Caner and Kilian, 2001;Pitarakis, in press;Fossati, 2012) has proposed refinements and enhancements. Important references are (Perron, 1989;Elliott et al, 1996;Ng and Perron, 2001) for unit roots tests, and (Leybourne and McCabe, 1994) for stationarity tests; see also Harvey (2001) for a review.…”
mentioning
confidence: 99%
“…See, for instance, Schwert (1989), Ng and Perron (1995), Agiakloglou and Newbold (1992), Agiakloglou and Newbold (1996), Elliott et al (1996), Ng and Perron (2001), Del Barrio Castro et al (2011), and Fossati (2012. The consensus is to use data-dependent methods.…”
Section: Introductionmentioning
confidence: 99%